1972
DOI: 10.1136/hrt.34.10.1018
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of atrial myxoma.

Abstract: Experience of I2 patients with atrial myxoma over a period of Io years is reviewed. Eleven patients had a left atrial tumour and one a right atrial tumour.Successful surgical removal was carried out in 9 (8 left, and I right). Three patients died before operation, the diagnosis having been made in life in 2 of them.Seven patients with left atrial myxoma have been followed for 5 to Io years after operation. Two died after 4 and 6 years, respectively, from probable neoplasia of the lungs without evidence of a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1978
1978
1996
1996

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…John Sutton et al, 1980;Walton et al, 1972). Although one patient in the Mayo Clinic study (St. John Sutton et al, 1980) required mitral valve replacement, severe damage of the atrioventricular valves in myxoma is rare (Croxson et al, 1972). The mitral insufficiency in our two patients remained mild on follow-up.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…John Sutton et al, 1980;Walton et al, 1972). Although one patient in the Mayo Clinic study (St. John Sutton et al, 1980) required mitral valve replacement, severe damage of the atrioventricular valves in myxoma is rare (Croxson et al, 1972). The mitral insufficiency in our two patients remained mild on follow-up.…”
Section: Discussionmentioning
confidence: 66%
“…The only late complications were residual mitral insufficiency in 2 patients (20%), associated with recurrence of a LAM in one (1 0%). The few long-term follow-up studies of myxoma have also found a similar, 5-14% incidence of recurrent LAM (Bulkley and Hutchins, 1979;Croxson et al, 1972;Richardson et al, 1979;St. John Sutton et al, 1980).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Since then 17 cases with 20 recurrences have been reported (Gerbode et al, 1967;Bahl et al, 1969;Kelly and Bhagmat, 1972;Walton et al, 1972;Maramhao et al, 1973;Read et al, 1974;Jugdutt et al, 1975;Dang and Hurley, 1976). However, results of only a few long-term studies of atrial myxoma cases have been published (Croxson et al, 1972;Hardin et al, 1974;Hedfors and Mogensen, 1974). Reviewing 12 cases of recurrent atrial myxomas, Read et al (1974) found that the average time to reoperation was only 31 months.…”
Section: Local Cardiac Recurrencementioning
confidence: 99%